Clara Maass, Yellow Fever and Human Experimentation - Chaves-Carballo, Enrique (Military medicine, 2013)
Clara Louise Maass, a 25-year-old American nurse, died of yellow fever on August 24, 1901, following experimental inoculation by infected mosquitoes in Havana, Cuba. The human yellow fever experiments were initially conducted by MAJ Walter Reed, who first used written informed consent and proved the validity of Finlay's mosquito-vector hypothesis. Despite informed consent form and an incentive of $100 in U.S. gold, human subjects were exposed to a deadly virus. The deaths of Clara Maass and two Spanish immigrants resulted in a public outcry and the immediate cessation of yellow fever human experiments in Cuba.